Traditional knowledge of agriculture in Bengali folk songs - Shehanaz Alam
India is a rich repository of cultural heritage and diversity, with a significant portion consisting of traditional folk songs. West Bengal has no exception and has got a wide variety of folk songs in every district of the state. This research has been conducted to identify the folk song relevant to agriculture and farmer$1 (Bs livelihood by understanding the contents with respect to themes. Emphasis has been rendered to explore the agricultural messages implied in the folk songs and to delve into any possibility to employ the folk songs as a tool for transfer of agricultural technologies. The research has been conducted by creating a compendium of the Bengali folk songs related to agriculture with experts$1 (Bassistance. These songs were analyzed by applying content analysis and represented in tabular forms depicting knowledge items with quantification. Since folk songs relevant to agriculture were considered, most of the songs belonged to the category of Karmasangeet (work song), followed by Tusu, Bhadu, Mahipal, Mecheni and others. Some of the songs carry traditional agricultural knowledge on cropping sequence, intercultural operation, plant protection, planting times, etc. Folk songs, whose primary idea was born to express the inner state of mind and break the monotony, can also be used for transforming the tacit knowledge into explicit one. Agricultural Extension, as a discipline, can very well employ the traditional folk media to impregnate the remotest of Indian villages with new technologies keeping intact the entertainment components